Torque recoil following screw insertion - Field, J. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Our ability to apply screws in a uniformly reproducible manner using “human torque control” has been shown to be very inconsistent. As a means of reducing this variability, torque-limiting devices are being utilized in select trauma and spinal applications. Cortical, cancellous and pedicle screws are now applied to a set, predetermined level of torque. It has been shown that extraction torque can be a little as 10% at the torque level at the time of application at plate removal 10 weeks after application. Using cadaveric specimens, the current study has evaluated the extraction torque immediately after application to a predetermined level. Regardless of the specimen, or location within the specimen, a significant difference was observed between the set application torque (1.5 Nm) and that obtained at the time of extraction (0.9 Nm). Some values were as low as 33% of the insertion value. This work suggests that in order to standardize interfragmentary compression, or bone plate fixation, we can not rely upon screw torque as the means of defining screw behaviour. Displacement control would appear to be the key to enable adaptation to the differing mechanical and biological nature of the bone and to overcome the recoil observed.
Keywords: Internal fixation; screw; torque